Modification of Prepared (Al 2024/Alumina/Mn) Composite by Laser Surface SiC Clad Layer - Marwa Juber; Amer Majeed; Mohammed Hamza; Thair Tawfiq (Engineering and Technology Journal, 2019)
The present work shows the cladding process of silicon carbide on the substrate of prepared composite (Al 2024/Alumina/Mn) by using a laser beam (pulsed Nd-YAG). To obtain the desired results, the best laser parameters were chosen. The parameters of the laser beam that have chief affected during the experiments in this work are peak power (1.9)kW, work frequency (8)Hz and pulse duration (5.3)ms, the preplaced powder technique favorite during a cladding process and the results in this work were proved by SEM, micro-hardness, EDS, and chemical corrosion tests. The results of the experimental work have shown that a micro-hardness increased about (28%) times for Aluminum/Alumina composite by silicon carbide cladding compared with the original value of micro-hardness, and thickness of the cladding layer was about (34μm). The resistance of corrosion was enhanced with about (35%) for the Aluminum/Alumina composite with SiC cladding.